Defibrotide suppresses brain metastasis by activating the adenosine A2A receptors. Issue 10 (10th August 2022) - Dong, Ce; Zhu, Lin; Yue, Xiongfei; Sun, Zheng; Wang, Cong; Ye, Zhanying; Pan, Baogen
Abstract : Brain metastasis is a devastating clinical condition globally as one of the most common central nervous system malignancies. The current study aimed to assess the effect of defibrotide, an Food and Drug Administration-approved drug, against brain metastasis and the underlying molecular mechanisms. Two tumor cell lines with high brain metastasis potential, PC-9 and 231-BR, were subjected to defibrotide treatment of increasing dosage. The metastasis capacity of the tumor cells was evaluated by cell invasion and migration assays. Western blotting was employed to determine the levels of tight junction proteins in the blood–brain barrier (BBB) including Occludin, Zo-1, and Claudin-5, as well as metastasis-related proteins including CXCR4, MMP-2, and MMP-9. The in-vitro observations were further verified in nude mice, by monitoring the growth of xenograft tumors, mouse survival and brain metastasis foci following defibrotide treatment. Defibrotide inhibited proliferation, migration, invasion, and promotes lactate dehydrogenase release of brain metastatic tumor cells, elevated the levels of BBB tight junction proteins and metastasis-related proteins. Such beneficial role of defibrotide was mediated by its inhibitory action on the SDF-1/CXCR4 signaling axis both in vitro and in vivo, as CXCR4 agonist SDF1α negated the anti-tumoral effect of defibrotide on mouse xenograft tumor growth, mouse survival and brain metastasis. Defibrotide inhibits brain metastasis through activating the adenosine A2A receptors, which in turn inhibits the SDF-1/CXCR4 signaling axis. Our study hereby proposes defibrotide as a new and promising candidate drug against brain metastasis of multiple organ origins.